The Actuality of Impulses, Perceptions, Manipulations and Solutions in Social Interactions among Diverse Religious Groups - Ramdhani, Indra; Qomaruzzaman, Bambang (Jurnal Iman dan Spiritualitas, 2024)
This research aims to understand residents' efforts to live their daily lives and establish social relationships with individuals of different religious beliefs, as well as to explore the formation of individual concepts and thoughts in interacting with their environment. In this context, differences in religion or belief can create social interactions that are associative or dissociative in nature. The authors will answer related questions, patterns of social interaction, impulses, perceptions, manipulation of individuals in social interactions, and the resolution of final actions regarding religious differences in the Sirnagalih sub-district, Indihiang, Tasikmalaya City. This research uses qualitative research with field methods and uses a sociology of religion approach. The results of the research show that social interaction between religious communities in the Sirnagalih sub-district, Indihiang sub-district, Tasikmalaya City occurs in an associative (unification) pattern where mutually beneficial interactions occur between individuals and each other between Muslims, Protestants and Catholics. The social processes that occur in the daily lives of Muslims, Protestants and Catholics, prioritize aspects of togetherness and harmony based on common or shared interests. The emergence of a slight dispute in the process of social interaction among citizens can be resolved immediately by involving a third party, namely the local government, by prioritizing forms of interaction in accommodation, namely mediation, compromise and tolerance.